Leveraging Life Cycle Cost Analysis (LCCA) for Optimized Decision Making in Adobe Construction Materials - Jorge Albuja-Sánchez; Andreina Damián-Chalán (Applied Sciences, 2024)
Adobe construction is a longstanding practice in South America and is characterized by its affordability, accessibility, and ecological sustainability. However, the decision-making process regarding the choice of construction materials often relies on subjective factors, disregarding economic implications throughout the life cycle of a building. This study aimed to introduce life-cycle cost analysis (LCCA) as a valuable tool for optimizing decision making in the context of adobe construction materials in South America. This study emphasizes the significance of considering the life-cycle costs associated with adobe construction materials and their impact on decision-making processes. A comprehensive case study was conducted in South America to examine the various adobe construction scenarios. The life-cycle costs of different adobe materials and their associated maintenance strategies were assessed over a period of several decades, considering factors such as material acquisition, construction, maintenance, and repair. The values used in this study are specific to Ecuador, the country where the investigation was conducted.